Nutrition Education for Non-Health University Students in Indonesia: A Literature Review - Rusdatul Isma; Judhiastuty Februhartanty; Hendra Susanto (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Nutrition education is a method used to enhance knowledge and improve attitudes and practices regarding nutrition. Although studies prove its effectiveness among school students, there is a lack of evidence showing the effect of nutrition education implemented among university students, moreover those in non-health fields. This article examined various nutrition education programs designed for non-health university students in Indonesia to improve their nutritional knowledge, attitudes, and practices. The literature search was conducted using Google Scholar and Research Gate databases with the keywords in Bahasa Indonesia